Awareness and Knowledge About Screening Tests for Cervical Cancer in Patient Attending Obstetrics and Gynaecology Out Patient Department at a Tertiary Care Hospital in Lalitpur - Maharjan, Meenu; Tuladhar, Heera (Medical Journal of Shree Birendra Hospital, 2018)
Introduction: Cervical cancer is the leading cause of cancer deaths for women worldwide. Early diagnosis of cervical cancer may be done by a simple and cost effective technique of Pap smear. The morbidity and mortality could be significantly reduced with an active cervical cancer screening programme. Methods: A cross sectional interview based study was done among 200 patients attending Obstetrics and Gynaecology OPD of one of the tertiary care hospital at Lalitpur, to assess the knowledge and awareness of patient regarding screening methods of cervical cancer and its prevention and early detection. Results: Among all the participants, 76.5% (n-153) were literate and 23.5% (n-47) were illiterate. Only 41% had heard about the Pap test and only 1% had heard about other methods of screening test like VIA(Visual Inspection with Acetic acid). Only 16% think that infection of the genital tract and 12.5% think that multiple partners is the leading cause of cervical cancer. Among them 51% (n-102) think that regular screening will prevent cervical cancer. But only 22.5% (45) had done Pap smear once and 67% did not know the risk factor of cervical cancer. Only 7% had heard of HPV vaccination but did not know details about it. Conclusions: There is very low level of knowledge about cervical cancer, Pap smear and HPV among the participants attending Obstetrics and Gynaecology OPD. For using Pap smear as a preventive method for cervical cancer, it is necessary to inform women about cervical cancer and the Pap smear test. An aggressive campaign with in depth teaching about cervical cancer by media and health care providers is mandatory.